FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN RUMAH TANGGA PETANI MELAKUKAN ALIH KOMODITI PADI SAWAH KE PERIKANAN DI DESA LIMAN SARI KECAMATAN BUAY MADANG TIMUR - Munajad (Jurnal Bakti Agribisnis, 2019)
The objectives of this study were to: 1) analyze the factors that influence farmers to transfer lowland rice commodities to fisheries, 2) calculate how much the difference in income received by farmer households from lowland rice commodity transfers to fisheries. The results showed that the factors that influenced the decision of the farmer household in transferring lowland rice commodities to fisheries at the test level up to 20% were farmers' income (4.3%), total production (12.9%) and farming risk (12.6. %), while the land area owned has no significant effect, while the results of statistical analysis using the Wilcoxon sign test analysis, obtained the value of Zhitung = -5,373 <Ztabel with p value (Asymp sign 2 tailed) = 0,000 which is less than the critical value of research 0, 05. This shows that the income of farmers who change the commodity of lowland rice to catfish farming is greater, namely Rp. 94,833,642 per year per hectare compared to income from lowland rice farming that does not change its land function, namely Rp. 25,154,791, - per year per year. acres.